2014
DOI: 10.1073/pnas.1318405111
|View full text |Cite
|
Sign up to set email alerts
|

Unified superresolution experiments and stochastic theory provide mechanistic insight into protein ion-exchange adsorptive separations

Abstract: Chromatographic protein separations, immunoassays, and biosensing all typically involve the adsorption of proteins to surfaces decorated with charged, hydrophobic, or affinity ligands. Despite increasingly widespread use throughout the pharmaceutical industry, mechanistic detail about the interactions of proteins with individual chromatographic adsorbent sites is available only via inference from ensemble measurements such as binding isotherms, calorimetry, and chromatography. In this work, we present the dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
124
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(134 citation statements)
references
References 70 publications
5
124
0
Order By: Relevance
“…fcsSOFI analysis was applied to image heterogeneous pore distribution and diffusion within agarose hydrogels, which are used broadly in cell culture growth, electrophoretic and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 chromatographic separations, 9,36 diffraction-limited position of emitters that are primarily trapped within pores (Figure 2a-c). In contrast, fcsSOFI analysis revealed the heterogeneous distribution of bright areas where beads are free to diffuse (i.e.…”
Section: Experimental Application Of Fcssofi To Agarose and Liquid Crmentioning
confidence: 99%
“…fcsSOFI analysis was applied to image heterogeneous pore distribution and diffusion within agarose hydrogels, which are used broadly in cell culture growth, electrophoretic and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 chromatographic separations, 9,36 diffraction-limited position of emitters that are primarily trapped within pores (Figure 2a-c). In contrast, fcsSOFI analysis revealed the heterogeneous distribution of bright areas where beads are free to diffuse (i.e.…”
Section: Experimental Application Of Fcssofi To Agarose and Liquid Crmentioning
confidence: 99%
“…Because adsorption heterogeneity is observed even with uniform adsorbate populations and at very low loadings [20], it is likely that inherent heterogeneity of the adsorbent surface commonly plays the larger role. Adsorbent heterogeneity can arise from a range of potential causes, including steric accessibility and constraint, surface entropy and mobility [13], and the stochastic clustering of ligands on the adsorbent surface [21]. We have found that while adsorbents based on pre-organized, penta-valent clustered-charge ligands show higher protein affinity and capacity than adsorbents of the same total density of charge randomly distributed, isotherms for protein adsorption even on these nominally-homogeneous adsorbents show heterogeneity [12].…”
Section: Introductionmentioning
confidence: 99%
“…We have found that while adsorbents based on pre-organized, penta-valent clustered-charge ligands show higher protein affinity and capacity than adsorbents of the same total density of charge randomly distributed, isotherms for protein adsorption even on these nominally-homogeneous adsorbents show heterogeneity [12]. This observation further implicates adsorbent steric and surface mobility properties as a ubiquitous source of heterogeneity; especially as our recent single-molecule observations highlighted the role of both ligand clustering and steric availability with the porous support [21] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,12,13 These strong sites are evidence of heterogeneity in surface interactions, which can be related to tailing of chromategraphic peaks arising from a distribution of residence times on the surface. 12,14 Although FCS is a versatile technique for measuring diffusion at homogeneous interfaces, the technique has limitations for surfaces that exhibit adsorption heterogeneity or mixed relaxation kinetics (diffusion together with adsorption and desorption, for example). In the former case, when long-lived adsorption events occur during a segment of FCS data being used to measure the diffusion coefficient of moving molecules, one observes a long-lived tail in the autocorrelation that obscures the measurement of the surface diffusion coefficient.…”
mentioning
confidence: 99%